Exploring The Use of The Make a Match Technique in Teaching Reading Comprehension in Senior High Schools - Jamila, Qorinatul; Ferdiyanto, Feri; Zainuddin (IKIP Siliwangi, 2026)
Reading comprehension is a fundamental component of English as a Foreign Language (EFL) instruction at the senior high school level. However, reading lessons in many classrooms remain predominantly teacher-centered, providing limited opportunities for collaborative meaning construction. This study aims to explore the implementation of the Make a Match technique in teaching reading comprehension and to examine students’ responses during the learning process. The study employed a qualitative case study design conducted in an eleventh-grade class at MA Darul Lughah Wal Karomah. Data were collected through classroom observations, semi-structured interviews, and document analysis. The data analysis followed the interactive model proposed by Matthew B. Miles and A. Michael Huberman, including data condensation, data display, and conclusion drawing/verification. The findings show that the implementation of the Make a Match technique occurred through several stages: lesson introduction, preparation of card-matching activities, cooperative interaction during the matching process, and confirmation or reflection. Students’ responses were observed in three forms of engagement: behavioral engagement, cognitive engagement, and affective involvement. The findings indicate that the technique organizes classroom interaction through structured cooperative activities that encourage students to engage with reading texts collaboratively. This study contributes a process-oriented understanding of how cooperative learning structures shape interaction and student engagement in EFL reading classrooms.